The same story or a unique novel? Within-participant principal-component analysis of measures of training load in professional rugby union skills training - Weaving, D.; Dalton, N. E.; Black, C.; Darrall-Jones, J.; Phibbs, P. J.; Gray, M.; Jones, B.; Roe, G. A. B. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To identify which combination metrics of external and internal training load (TL) capture similar or unique information for individual professional players during skills training in rugby union using principal-component (PC) analysis. Methods: TL data were collected from 21 male professional rugby union players across a competitive season. This included PlayerLoad™, total distance, and individualized high-speed distance (>61% maximal velocity; all external TL) obtained from a microtechnology device (OptimEye X4; Catapult Innovations, Melbourne, Australia) that was worn by each player and the session rating of perceived exertion (RPE) (internal TL). PC analysis was conducted on each individual to extract the underlying combinations of the 4 TL measures that best describe the total information (variance) provided by the measures. TL measures with PC loadings (PCL) above 0.7 were deemed to possess well-defined relationships with the extracted PC. Results: The findings show that from the 4 TL measures, the majority of an individual`s TL information (first PC: 55-70%) during skills training can be explained by session RPE (PCL: 0.72-0.95), total distance (PCL: 0.86-0.98), or PlayerLoad (PCL: 0.71-0.98). High-speed distance was the only variable to relate to the second PC (PCL: 0.72-1.00), which captured additional TL information (+19-28%). Conclusions: Findings suggest that practitioners could quantify the TL of rugby union skills training with one of PlayerLoad, total distance, or session RPE plus high-speed distance while limiting omitted information of the TL imposed during professional rugby union skills training.